Optimizing firm value: the impact of intellectual capital with competitive advantage - Widayanto, Aditya Dwi Ramadhan; Harmono, Harmono; Apriyanto, Gaguk; Hidayatullah, Syarif (Jurnal Penelitian, 2023)
Managing firm value becomes crucial for ensuring shareholder interests. Investors rely on company information, particularly financial reports and ratios, to gauge performance before making investment decisions. Intellectual capital and competitive advantage emerge as key factors influencing firm value. This research aims to provide empirical evidence that intellectual capital has a significant effect on firm value with competitive advantage as a moderator. This study focuses on pharmaceutical companies listed on the Indonesia Stock Exchange. There are 12 such companies. We selected them based on having complete audited financial reports for the past 5 years. We collected data from audited financial reports of pharmaceutical companies listed from 2017 to 2021. The results suggest that the intellectual capital variable does not affect firm value. Meanwhile, partial testing carried out on indicators of intellectual capital found that only capital employed efficiency had a significant effect on firm value. Competitive advantage as proxied by inventory turnover does not affect firm value. However, competitive advantage as proxied by receivable turnover can have a significant influence on firm value.Â The research results show that managing intellectual capital efficiently will give rise to competitive advantage which has the impact of increasing firm value.